1999
DOI: 10.1159/000006980
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Effects of Persistent Hemodialysis Arteriovenous Access in Recipients of Renal Allograft

Abstract: In hemodialysis patients, large arteriovenous (AV) fistulas for vascular access may cause ventricular hypertrophy and high-output cardiac failure. The long-term cardiac consequences of functional AV fistulas in renal transplant patients are unclear. A precise knowledge of these consequences is important to decide if and when such fistulas should be closed in successfully transplanted patients. In this retrospective study including 61 stable renal transplant patients with adequate renal function (serum creatini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 9 publications
2
46
2
Order By: Relevance
“…It is also interesting to note that 42% of our closed AVF were proximal stulas, whereas these AVF represented only 13% of the total population. Our results are supported by de Lima et al, who speci cally studied the cardiac effect of persistent AVF in renal transplant patients (5). In a retrospective study, he compared left ventricular (LV) mass, cardiac index, ejection fraction, and proportion of patients with LV hypertrophy, in 39 patients with functioning stulas against 22 with closed stulas.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is also interesting to note that 42% of our closed AVF were proximal stulas, whereas these AVF represented only 13% of the total population. Our results are supported by de Lima et al, who speci cally studied the cardiac effect of persistent AVF in renal transplant patients (5). In a retrospective study, he compared left ventricular (LV) mass, cardiac index, ejection fraction, and proportion of patients with LV hypertrophy, in 39 patients with functioning stulas against 22 with closed stulas.…”
Section: Discussionsupporting
confidence: 82%
“…It is of course conceivable that only large AV stulas with high ows tend to remain patent and therefore contribute to cardiac abnormalities. This is partially con rmed by two series of renal transplant patients with patent AVF in which the mean AVF ows were respectively 900 § 350 and 1790 § 648 ml/mn (5,6). However, causes of left ventricular hypertrophy in end stage renal failure are numerous, including hypertension, anaemia, uremic status, and the presence of AVF.…”
Section: Discussionmentioning
confidence: 89%
“…Experience with arteriovenous dialysis fistulae does not suggest a high incidence of heart failure, despite significant shunt volumes. 15 Indeed, a reduction in left ventricular size and volume, along with impaired left ventricular diastolic filling, in patients with COPD has been reported, 16 perhaps the result of diminished right heart function and left ventricular underfilling because of static hyperinflation. 17 Thus, in theory, AVS creation may improve left ventricular filling and performance; however, heart failure because of arteriovenous fistula formation has been reported, 18,19 and despite the reduction in systemic vascular resistance, an increase in left ventricular stroke work after AVS creation has been shown.…”
Section: Bertog Et Al Percutaneous Arteriovenous Fistula Creation In mentioning
confidence: 99%
“…A possible concern therefore is that the ROX Coupler could cause or exacerbate LVH. Data from the HD population are conflicting with some studies reporting an increase in LV mass (Ori et al 14 ), whereas De Lima et al 29 and Gorgulu et al 30 reported no change. There are also multiple studies showing that closure of an AVF after renal transplantation results in favorable cardiac remodeling and a reduction in LVH.…”
Section: Holmanmentioning
confidence: 97%